Reprise d'initiative et éducation interculturelle chez les Amérindiens de l'Amazonie brésilienne (Etat d'Amazonas) - Olivier Meunier (Nantes Université, 2010)
The traditional transmission of knowledge in the societies concerned by orality and the Western model of the school can appear a priori dichotomist, which often contributed to their juxtaposed development and generally to a process of domination of the second to the first. In Brazil, following the republican process aiming at assimilate the Amerindian populations to the Nation during the 1970-1980, these last were organized to safeguard their territory and their cultural identity, which gave place from the 90' of the last decade at a generalization of an intercultural school education in the indigenous territories, opening the school with the indigenous sociocultural knowledge. By integrating traditional knowledge in teaching, the school model allowed these children distant from an "occidentalized" school culture, to connect the "communal" knowledge to the school knowledge. This system has a capacity to consider the plurality of the cultural differences. This one is not lived like a regressive mark of collective unconscious. It is on the contrary the recognition of the traditional cultures which conditions the desire of new knowledge and its appropriation, which could be also an answer for other countries, in particular at the pupils socially and culturally far away from the instituted school.